Utilization of UAV-Borne RGB Data for Monitoring Horses: Comparison of Classification Methods - Jech, Jakub; Komárková, Jitka; Sedlák, Pavel; Krátký, Martin (IEEE (Institute of Electrical and Electronics Engineers), 2023)
The paper describes utilizing remotely sensed RGB data to support monitoring horses in a natural environment on demand. Data are sensed using an unmanned aerial vehicle (UAV). UAVs provide very high spatial resolution data sensed at a low altitude on demand. Sensing is limited by weather conditions and legal rules only. Terrain does not need to be accessible. The paper provides a comparison of several pixel-based and object-based classification methods, namely Maximum Likelihood, Random Trees, SVM, and K-NN. Manual classification is used as a reference method.
Využití UAV-Borne RGB dat pro monitorování koní: Porovnání klasifikačních metod
Keywords: imagery; live animals monitoring; object-based classification; pixel-based classification; UAV; obrazová data; sledování živých zvířat; objektová klasifikace; pixelová klasifikace; UAV